Investigation of Aroma Release and Rheological Properties in Dairy Desserts with Reduced Fat Content - Müge Baysal; Yeşim Elmacı (Turkish Journal of Agriculture: Food Science and Technology, 2020)
Dairy desserts, which have an important place in Turkish cuisine, are mild, more digestible and have high nutritional value than dough and syrup desserts. In recent years, studies for developing these products have increased due to the increase in consumer demand for low and zero fat products for many different reasons such as nutrition, health and weight control. However, the reduction of fat in food products often leads to undesirable changes in the structural properties of foods, which affects consumer preference. Fat in the formulation of such products, affects the appearance, texture, mouthfeel, and especially flavor. To eliminate the problems associated with the reduction of fat content in foods, whey protein-pectin complexes, λ-carrageenan, κ-carrageenan, short and long chain inulin mixtures, starch substitutes are generally used. Changes in fat content of dairy desserts with the use of substitutes affect color, rheology, texture, sensory perception, aroma release and perception. Milk fat content is effective on sensory detection, in vivo flavor and flavor release in semi-solid dairy desserts. The milk fat content (whole-fat, low-fat or non-fat) used in the production of dairy dessert affects the rheological and sensory properties of the product, the taste intensity perceived in the mouth, flavor release, flow behavior, flavor and viscoelastic properties. According to the reviewed literature, in dairy desserts with reduced fat content, the thickener type and concentration (starch, κ-carrageenan, carboxymethyl cellulose) have been determined to cause perceptible changes in the product’s color, flavor and texture, and may alter the physical and structural properties of the product. In this review, it was aimed to examine the aroma release and rheological properties of dairy desserts with reduced fat content by using fat substitutes.